Mathematics Discourse in Secondary Teacher Candidates’ Lessons: A Mixed Methods Analysis - Ashley Schmidt; Christopher R. Rakes; Sarah B. Bush; Robert N. Ronau; Siddhi Soni; Molly Fisher; Lisa Amick; Julian Viera; Farshid Safi (Education Sciences)
Meaningful discourse in the mathematics classroom involves creating a learning community that empowers students to articulate their reasoning and make sense of the contributions of their peers while advancing the learning of mathematics for the entire class. This study assessed the degree to which secondary mathematics (Grades 7–12) teacher candidates incorporated discourse into their lessons and the factors influencing their decisions. An explanatory mixed methods design was used, in which data were collected sequentially. Lesson videos were analyzed, followed by interviews of teacher candidates with high-discourse lessons. This study found that participants showed significant growth in their use of effective teaching practices from the beginning of the semester to the end of the semester, including mathematics discourse. The interviews revealed four contributing factors: intentional effort, learning experiences, professional relationships, and pedagogical knowledge. Understanding the experiences of teacher candidates during their own learning of mathematics, their mathematical identities, and beliefs about mathematics could help generate knowledge regarding the implementation of mathematics discourse and other reform-based practices in teacher instruction.